Morphological, acoustic and genetic divergence in the bladder grasshopper Bullacris unicolor. Issue 6 (2nd November 2017) - Sathyan, Rekha; Engelbrecht, Adriaan; Couldridge, Vanessa C.K.
Abstract : Although the processes that promote biodiversity remain poorly understood, geographic variation resulting from selection and/or neutral processes is thought to be a precursor to allopatric speciation. An examination of intraspecific divergence in multiple traits and their co-variation is an essential part of understanding the origin of new species. Here we investigate patterns of geographic variation in acoustic, morphological and genetic characters of allopatric populations of the bladder grasshopper Bullacris unicolor . We found significant geographic variation in both temporal and frequency components of male advertisement calls, as well as in morphological variables of males and females. However, acoustic characters were much more strongly differentiated between populations than were morphological characters, with no correlation between acoustic and morphological traits. Furthermore, analysis of the mitochondrial DNA marker cytochrome c oxidase I indicated strong genetic structuring, pointing towards genetic isolation among populations in the absence of isolation by distance. Furthermore, we found genetic distance was significantly correlated with morphological differentiation, but not with acoustic differentiation. The high levels of variation in male advertisement calls between populations, as well as the lack of association between acoustic and genetic distance, suggests that divergence in acoustic traits cannot be attributed to genetic features, and is more likely due to alternative selective pressures, such as mate choice or the ecological environment. Our results further suggest that morphological and acoustic features are uncorrelated at the intraspecific level and appear to be evolving under separate selective pressures.